Impact of Russia-Ukraine War Crisis on Indian Economy - Das, Pradip Kumar (Archives of Business Research, 2023)
pThe war between the two neighboring countries, Russia and Ukraine, is a bleak blow to the world economy begetting sluggish growth and rapid inflation. Sanctions advocated on Russia due to the dissention beseem to have an impact on the Indian economy in particular and global economy in general through convulsion of supply chains. India has close ties with both the countries. During the retrieval way of economy from the pandemic, purported crunch in Ukraine and Russia which dispatch disparate commodities has posed novel challenges to India’s economic resilience. Ukraine and Russia produce elephantine share of global exports of wheat. Discord between the countries definitely spawns prices of diesel, petrol, wheat, vegetable oils and many other commodities to skyrocket. Ineluctably, most of the Indians have curtailed fried food and even vegetables. Consumers sense the bite owing to price inflation. In the event of such menacing dilemma, this paper is a modest attempt to examine the impact of Russia-Ukraine war on Indian economy. The results of the study consummated through documentation review and critical approach, secondary data relevant to the context unveil slow Indian economic growth and development springing disruption to the parallel sanity of the international structure seesawing global and provincial geopolitical estimation. The paper broaches that clamant initiatives and recipes have to be shouldered by the civic society, particularly the leading states and non-state entities to heel a meteoric death to the extant Russia-Ukraine war. nbsp;nbsp;nbsp;/p